" Cyberspace Institutions in the Middle East: Iran and Israel as a model " - Alnasiry , Hiba a. khattab; Merei, Muthanna Faeq (Tikrit Journal For Political Science, 2022)
The trend towards enhancing cyber capabilities is one of the priorities of the Iranian and Israeli governments, especially in recent years, which witnessed great competition between them in the context of preserving vital interests and expanding influence, as Iran sought through developing cyber capabilities not only for defensive or offensive purposes, but also to limit the freedom of information flow To the citizens, which caused the outbreak of revolutions, most notably those that occurred in 2009, in contrast to Israel, which supported the development of national cyber capabilities with the aim of maintaining superiority in the electronic field over other neighboring countries, as well as providing another factor to deter others in the event of entering into a cyber confrontation, especially by Iran.